A Comparison of Maternal and Fetal Outcomes of Pregnancies Complicated by Moderate to Severe Thrombocytopenia Caused by Gestational Thrombocytopenia Preeclampsia / HELLP Syndrome and Immune Thrombocytopenic Purpura - Suna Özdemir; Hüseyin Görkemli; Ali Acar; Çetin Çelik; Erkan Kayıkçıoğlu (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: Aim of this study was to compare obstetric risk factors and complications, and outcomes of pregnancies associated with moderate to severe thrombocytopenia caused by gestational thrombocytopenia (GT), preeclampsia/HELLP syndrome, and immune thrombocytopenic purpura (ITP). STUDY DESIGN: The study was composed of 135 women with a platelet count below 100.000/mm3. The characteristics and clinical details of all women and neonatal were recorded during their hospital course. RESULTS: The ratio of severe thrombocytopenia was observed significantly lower in GT group compared with preeclampsia / HELLP syndrome and ITP groups. Higher rates of oligohydroamnios, IUGR, and placental abruption were found among patients in preeclampsia+HELLP syndrome group. The rates of Apgar scores (<7) at 1 and 5 min, pH values (<7,2), and amniotic fluid with meconium were higher in preeclampsia / HELLP syndrome group. Neonatal thrombocytopenia was recorded in a total of 5 infants. CONCLUSION: The thrombocytopenia with preeclampsia/HELLP syndrome had less favorable obstetric and fetal outcomes.